ANGKA KEJADIAN ACUTE KIDNEY INJURY PADA KEHAMILAN: NARRATIVE REVIEW - Saranitha Windy Oktavia Malau (Universitas Udayana, 2022)
Incidence of acute kidney injury (AKI) in pregnancy still plays an important role in maternal and fetal morbidity and mortality. However, in some developing countries the maternal and fetal mortality rates have started to decline and are still increasing in developed countries. This study was conducted to determine the incidence of AKI in pregnancy in several countries. This study was to determine incidence of AKI in pregnancy using a narrative review research model, in which a worldwide literature search was carried out through the e-library, such as pubmed and proquest which discusses the incidence of AKI in pregnancy. After the journals that match the inclusion criteria are collected, they are analyzed and interpreted in a narrative form. There were 10 journals that matched the inclusion criteria by including the total number of samples and the number of new samples, where the incidence of AKI in pregnancy was found in American countries, China, Indian countries and African countries. Based on this study, the range of incidence of acute kidney injury in pregnancy from several countries was 0.07% to 8.1%. The incidence rate in the American countries began to decline by 6.15% to 0.08%, but based on the average it still increased from 0.04% to 0.12%. In China, it was found 0.81% to 3.68%, Indian countries 2.78% to 0.07%, and African countries 8.1% to 2.29%. Keywords : Incidence, Acute Kidney Injury in pregnancy, Complications in pregnancy